Polymorphism of carbon oxidation of drugs and clinical implications. Issue 6138 (2nd September 1978) - Sloan, T P; Mahgoub, A; Lancaster, R; Idle, J R; Smith, R L
Abstract : Eight volunteers previously phenotyped for their ability to hydroxylate debrisoquine (four extensive metabolisers (EM), four poor metabolisers (PM) were investigated for their metabolic handling of guanoxan and phenacetin. All three drugs are oxidised at carbon centres. Oxidative dealkylation of phenacetin was determined by measuring the rate of formation of paracetamol. The EM subjects excreted mostly metabolites of guanoxan (mean 29% of dose), whereas the PM group excreted large amounts of unchanged drug (48% of dose). The rate of formation of paracetamol was noticeably slower in the PM group, and, when analysed by minimum estimates of apparent first-order rate constants, the difference between the two phenotypes was significant. Thus the hydroxylation defect shown for debrisoquine metabolism carries over to the oxidative metabolism of phenacetin and guanoxan. Some 5% of the population are genetically defective hydroxylators of drugs. Thus methods for evaluating the metabolism of new drugs in respect of usage and side effects need to be revised.